Kinetic interaction regularity of bismuth-boron glasses with orthophosphoric acid. - F. N. Karachevtsev; V. A. Kutvitsky; O. V. Sorokina (Тонкие химические технологии)
Have been carry out research of interaction kinetic of bismuth-boron glasses consisting of: 70% Bi2O3, 30% Bi2O3; 70% Bi2O3, 27% Bi2O3, 3% MoO3; 70% Bi2O3, 26.94% Bi2O3, 3.06% GeO2 with 87% orthophosphoric acid. On initial interaction stage (under 3 min) establish a quota be chemistry reaction. At increase time (higher 10 min) of interaction primary role in heterogeneous process play stage of diffusion through lay at a surface.